Polyethylene/Silver-Nanofiber Composites: A Material for Antibacterial Films - Rabagliati-Canessa, F; Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L; Zapata-Ramirez, P (Elsevier Ltd, 2016)
Silver nanofibers (Ag-Nfbs) ~ 80 nm in diameter were synthesized by hydrothermal treatment. The nanofibers (3 and 5 wt%) were added in the initial feed together with the catalytic system. Polymerizations in an ethylene atmosphere were performed, yielding PE nanocomposites in situ with 3 and 5 wt% content of Ag-Nfbs. The antibacterial effect of the silver-nanofiber composites was evaluated after incubation of Escherichia coli ATCC 25923 for 8 h on their surface. Bacterial viability tests showed that the silver-nanofiber composites inhibited the growth of Escherichia coli ATCC 25923 by 88 and 56%. This behavior is attributed to increased silver ions release from the nanocomposite. TEM analysis showed that the antibacterial effect is associated with membrane disruption but not with changes in shape. © 2016 Elsevier B.V.